2023
DOI: 10.1177/20551029221149282
|View full text |Cite
|
Sign up to set email alerts
|

Trait mindfulness and sleep: Interactions between observing and nonreactivity in the association with sleep health

Abstract: The current study investigated the associations between trait mindfulness and sleep health and examined the interactions between theoretically related mindfulness subscales. Participants ( n = 162, Mage = 19.93) reported trait levels of mindfulness and sleep was assessed using questionnaires and actigraphy. Higher mindfulness scores in awareness, nonreactivity, and nonjudgment were associated with better sleep health. The associations between observing and sleep health were moderated by nonreactivity. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In other studies, in undergraduate samples, acting with awareness and non-judgement were associated with higher sleep quality on the PSQI, while observing had negative effects. 18 , 74 Recent work in an undergraduate student sample found that the associations between observing and sleep health were moderated by non-reactivity : observing was associated with worse sleep at lower levels of non-reactivity , but better sleep health at higher levels of non-reactivity . 28 …”
Section: Discussionmentioning
confidence: 99%
“…In other studies, in undergraduate samples, acting with awareness and non-judgement were associated with higher sleep quality on the PSQI, while observing had negative effects. 18 , 74 Recent work in an undergraduate student sample found that the associations between observing and sleep health were moderated by non-reactivity : observing was associated with worse sleep at lower levels of non-reactivity , but better sleep health at higher levels of non-reactivity . 28 …”
Section: Discussionmentioning
confidence: 99%
“…The authors further investigated objective sleep parameters—measured via actigraphy—and found no significant association with trait mindfulness. However, recently, it was shown that a sleep health score, as quantified by six domains including two subjective measures and four actigraphy-based measures of sleep, namely sleep regularity, duration, timing, and efficiency, was positively associated with trait mindfulness [ 19 ]. While actigraphy offers a convenient method for tracking sleep patterns, the more reliable gold standard to measure objective sleep is polysomnography, which depends on electroencephalographic (EEG) measures of brain waves.…”
mentioning
confidence: 99%